Mempertahankan Eksistensi dan Peluang Melalui Komunitas Indonesian Social Blogpreneur - Berta, Ani; Mahardika, Prada Hafiz (Jurnal Pustaka Komunikasi, 2025)
Currently, the popularity of blogs is starting to decline but they still hold potential for use by online communities, including the blogger community. This study analyzed and examined the Blogger Community, specifically the Indonesian Social Blogpreneur Community, better known as the ISB Community. The purpose of this study was to explore the various opportunities for earning income in the digital realm, particularly through blogging opened opportunities for related professions such as content writing for websites, social media management, and content creation on other platforms. The study used a qualitative with case study method with Community of Practice concept. The research data were obtained from interviews with four bloggers who were members of the ISB Community and had received various opportunities from their blogging activities. The results show that the community plays a significant role in helping its members explore their potential and seize opportunities. Consistent participation in community activities has positively impacted bloggers, allowing them to develop their skills. The implications of this study suggest that continuous capacity building through various programs designed to foster a growth mindset is an effective way to empower community members.